2012
DOI: 10.1186/1556-276x-7-501
|View full text |Cite
|
Sign up to set email alerts
|

Magnetite nanoparticles for functionalized textile dressing to prevent fungal biofilms development

Abstract: The purpose of this work was to investigate the potential of functionalized magnetite nanoparticles to improve the antibiofilm properties of textile dressing, tested in vitro against monospecific Candida albicans biofilms. Functionalized magnetite (Fe3O4/C18), with an average size not exceeding 20 nm, has been synthesized by precipitation of ferric and ferrous salts in aqueous solution of oleic acid (C18) and NaOH. Transmission electron microscopy, X-ray diffraction analysis, and differential thermal analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 25 publications
3
29
0
2
Order By: Relevance
“…As reported by Mahdavi et al [27] for functionalized MNPs with oleic acid, XRD data showed negligible effects of this fatty acid on the XRD spectra data. The morphology and particle size of nanoparticles were similar to those reported by Anghel et al [15] for functionalized magnetite (Fe 3 O 4 /C 18 ), that is, the same type of functionalization (oleic acid) done in the present work. In the Mössbauer spectroscopy, and at room temperature, spectra showed a gradual passage from bulk-like to superparamagnetic (SPM) behavior, as the average size of the particles decrease, a striking characteristic of the superparamagnetic nature of nanoparticles [28].…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…As reported by Mahdavi et al [27] for functionalized MNPs with oleic acid, XRD data showed negligible effects of this fatty acid on the XRD spectra data. The morphology and particle size of nanoparticles were similar to those reported by Anghel et al [15] for functionalized magnetite (Fe 3 O 4 /C 18 ), that is, the same type of functionalization (oleic acid) done in the present work. In the Mössbauer spectroscopy, and at room temperature, spectra showed a gradual passage from bulk-like to superparamagnetic (SPM) behavior, as the average size of the particles decrease, a striking characteristic of the superparamagnetic nature of nanoparticles [28].…”
Section: Discussionsupporting
confidence: 89%
“…Functionalized Fe 3 O 4 /C 18 nanoparticles without propolis extract present ability for inhibiting the adherence of MRSA strains, as already reported by Anghel et al [15], nevertheless always inferior when compared to those samples also functionalized with propolis extract, which reveals the importance of this extract on the activity.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Magnetite is one of the most used inorganic nanomaterials for variable biomedical, both clinical and research applications, including the development of novel antimicrobial strategies, due to their good biocompatibility [12] and intrinsic antimicrobial properties, as well as their quality to act in synergy with other antimicrobial drugs (such as antibiotics but also natural products that may have antimicrobial effects, such as plant-derived compounds and essential oils) or to act as effective drug carriers [13][14][15].…”
Section: Introductionmentioning
confidence: 99%